PENGARUH EKSTRAK AKAR GINGSENG JAWA DALAM BERBAGAI KADAR TERHADAP SINTESIS PROTEIN SERUM TIKUS - Tri Nurhariyati; Dwi Winarni; Salamun Salamun; Y Sri Wulan Manuhara; Saikhu Ahmad Husen (The East Java Biological Society, 2000)
The aim of this research was identifying the stimulation serum protein synthesis following the treatment of Java Gingseng (Talinum paniculatum Gaertn) root extract in varying concentration. This research used 12 male rats of 8-9 weeks, divided into 4 groups. First group as control, second group to five group were administratered with Java gingseng root extract equal with 3.5, 10.5, and 21 mg dry roots / 100g BW / day per oral for 14 days. Blood serum was collected for electrophoresized at the end of treatment. Electrophoresis was conducted with 7% SDS-PAGE method. Gel stained in 0.25% Coomasie Brilliant Blue and it followed densitometry on band in gel to comparing those quantitatively. The result show the effect on the level of serum protein whose MW 29. Highest stimulation of protein synthesis (2.2 times than control) have been reached at treatment with extract that equal with 3,5 mg dry root/ 100 g BW/ day. Increasing Java gingseng root extract wasn’t followed by increasing of stimulation protein synthesis level.